Pengaruh Return On Equity (Roe) Dan Return On Assets (Roa) Terhadap Kualitas Laba Pada Perusahaan Real Estate Management And Development Periode 2021-2024 - Afriadi, Alief; Lestari , Nurlaela Eva Puji (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2025)
The Real Estate Management and Development company is a company that has good development and prospects for the future. To assess the company's performance, one can refer to the financial statements. A good financial statement reflects quality profits. Profits are considered of quality if they have stability and predictability. Profits can also be measured through financial ratios such as Return On Equity (ROE) and Return On Assets (ROA). The objective of this study is to determine whether each independent variable has an effect on the dependent variable and whether the independent variables collectively have an effect on the dependent variable. The data collection method in this study uses quantitative research with secondary data taken from the financial statements of Real Estate Management and Development companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. In this research, data processing is assisted by SPSS version 21.0. The results of this study indicate that the ROE variable (X1) does not have a partial effect on Earnings Quality (Y), and the ROA variable (X2) does not have a partial effect on Earnings Quality (Y) either. Simultaneously, the independent variables have an effect on the dependent variable.